Nutrition Info and Other Front-of-Package Labels and Simulated Food and Beverage Purchases: A Randomized Clinical Trial - Grummon, Anna H.; O'Sullivan, Kevin; Petimar, Joshua; Lee, Cristina J.Y.; Zeitlin, Amanda B.; Cleveland, Lauren P.; Collis, Caroline; Musicus, Aviva A.; Tiefenbeck, Verena; Fleisch, Elgar; Block, Jason P. (JAMA Network Open, 2025)
Importance: In January 2025, the US Food and Drug Administration (FDA) released a proposed rule to require front-of-package nutrition information (Nutrition Info) labels that would signal when packaged foods contain low, medium, or high levels of saturated fat, sodium, or added sugars (ie, nutrients of concern). However, it is unknown whether this labeling system would encourage healthier food and beverage purchases. Objectives: To test whether Nutrition Info labels similar to those proposed by the FDA could lead to healthier food and beverage purchases compared with other existing or proposed labeling systems. Design, Setting, and Participants: This randomized clinical trial was conducted online from October 31 to November 21, 2024. Participants included a national sample of US adults who reported being their household's primary shopper. Data were analyzed from November 26, 2024, to August 27, 2025. Intervention: Participants were randomized to exposure to 1 of 6 front-of-package labeling systems: positive labels (ie, labels that communicate only the positive attributes of a food) only, Nutrition Info labels (similar to the FDA's proposal), positive plus Nutrition Info labels, "High In"labels (similar to designs the FDA tested to signal when products contain high levels of nutrients of concern), positive plus High In labels, or spectrum labels (similar to designs used internationally rating products from least to most healthy). Main Outcomes and Measures: Participants shopped for foods and beverages in a large, simulated online grocery store. The primary outcome was healthfulness of participants' food and beverage selections, assessed using the United Kingdom's Ofcom Nutrient Profiling Model scores (ranging from 0 to 100, with higher scores indicating healthier choices). Scores were compared between groups using the average differential effect (ADE). Results: A total of 5636 participants completed the trial (3400 [60%] women; mean [SD] age, 40.3 [12.6] years). The spectrum labels led to healthier purchases compared with both the positive labels only (ADE, 2.42; 95% CI, 1.66-3.17; P <.001) and all other labeling systems (range of ADEs, -1.87 [95% CI, -2.63 to -1.11] to -2.45 [95% CI, -3.21 to -1.69]; P <.001). By contrast, the Nutrition Info, positive plus Nutrition Info, High In, and positive plus High In labels did not lead to healthier purchases compared with the positive labels only (range of ADEs, -0.04 [95% CI, -0.80 to 0.72; P =.92] to 0.54 [95% CI, -0.22 to 1.30; P =.16]). Label effects did not differ by nutrition literacy, household income, or educational attainment. Conclusions and Relevance: In this randomized clinical trial of food labeling systems, spectrum labels that rate foods from least to most healthy led to healthier purchases than positive labels and Nutrition Info labels similar to those proposed by the FDA. These findings suggest that spectrum labels may be more promising than both existing positive labels and the FDA's proposed labels for promoting healthier food purchases. Trial Registration: ClinicalTrials.gov Identifier: NCT06516627
CRIS-Team Scopus Importer:2025-10-31